PELATIHAN PENINGKATAN KUALITAS PEMBELAJARAN BAHASA INDONESIA/MEMBACA PERMULAAN BAGI GURU SDN GRUDO 4 NGAWI: - - . Mukhzamilah; . Mulyono; . Yunisseffendri; Trinil Dwi Turistiani; Hespi Septiana (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2023)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education through formal education, basic education, and secondary education. Teachers must have a minimum academic qualification of bachelor (S1) or diploma (D-IV), master competence (pedagogic, professional, social, and personality), have an educator certificate, be physically and mentally healthy, and have the ability to realize national education goals. The method in this activity is training and assistance in the preparation of learning tools and media. In the early stages, participants are given explanations or lectures related to concepts and knowledge about language learning. In the next stage, participants are invited to discuss the problems they face when carrying out learning in class. In order for the activity to be directed, participants are given a worksheet during the mentoring which contains an analysis of the learning that has been done and efforts to improve it. To solve the problems faced by the target audience, namely teachers, it is carried out through community service with a participatory approach. The results obtained during the program received positive responses from the training participants (teaching staff) regarding the programs that had been implemented by the research team so far. This response is evidenced by the number of agreements from the training participants, and also the many positive responses from the participants which they filled in the questionnaire column. Keywords: Teachers, Training, Quality Improvement, Indonesian Language